Deletion at the SLC1A1 glutamate transporter gene co‐segregates with schizophrenia and bipolar schizoaffective disorder in a 5‐generation family12. Issue 2 (22nd January 2013) - Myles‐Worsley, Marina; Tiobech, Josepha; Browning, Sharon R.; Korn, Jeremy; Goodman, Sarah; Gentile, Karen; Melhem, Nadine; Byerley, William; Faraone, Stephen V.; Middleton, Frank A.
Abstract Growing evidence for genetic overlap between schizophrenia (SCZ) and bipolar disorder (BPD) suggests that causal variants of large effect on disease risk may cross traditional diagnostic boundaries. Extended multigenerational families with both SCZ and BPD cases can be a valuable resource for discovery of shared biological pathways because they can reveal the natural evolution of the underlying genetic disruptions and their phenotypic expression. We investigated a deletion at the SLC1A1 glutamate transporter gene originally identified as a copy number variant exclusively carried by members of a 5‐generation Palauan family. Using an expanded sample of 21 family members, quantitative PCR confirmed the deletion in all seven individuals with psychosis, three "obligate‐carrier" parents and one unaffected sibling, while four marry‐in parents were non‐carriers. Linkage analysis under an autosomal dominant model generated a LOD‐score of 3.64, confirming co‐segregation of the deletion with psychosis. For more precise localization, we determined the approximate deletion end points using alignment of next‐generation sequencing data for one affected deletion‐carrier and then designed PCR amplicons to span the entire deletion locus. These probes established that the deletion spans 84, 298 bp, thus eliminating the entire promoter, the transcription start site, and the first 59 amino acids of the protein, including the first transmembrane Na2+/dicarboxylate symporter domain, one of the domains that perform the glutamate transport action. Discovery of this functionally relevant SLC1A1 mutation and its co‐segregation with psychosis in an extended multigenerational pedigree provides further support for the important role played by glutamatergic transmission in the pathophysiology of psychotic disorders. © 2013 Wiley Periodicals, Inc.